Kajian Kualitas Pelayanan Menuju Peningkatan Kepuasan Pelanggan Eksternal Fakultas Pertanian Universitas Mataram - Tajidan Tajidan; Anwar Anwar; Hery Haryanto; Bambang Dipokusumo (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
The purpose of this study was to measure the service quality of the implementing unit of higher education institutions, to measure the level of external customer satisfaction, and to analyze the relationship between service quality and external customer satisfaction levels. To achieve these objectives, research was carried out by combining observation methods, distributing questionnaires to 200 external customers, focus group discussions, and public consultations. As the unit of analysis in this study, external customers consist of parents of students, alumni, graduate users, and cooperation partners. The collected data were analyzed using descriptive statistical analysis, and non-parametric statistical analysis, namely Spearman rank correlation. The results showed: the service quality of higher education implementing units is identical to the level of satisfaction of external customers; achievement of the level of external customer satisfaction is from good to very good; external customer satisfaction of alumni and graduate users is in a good position, while external customers of students' parents and cooperation partners are in a very good position.